2011
DOI: 10.1136/bjo.2010.194217
|View full text |Cite
|
Sign up to set email alerts
|

The utility of relative afferent pupillary defect as a screening tool for glaucoma: prospective examination of a large population-based study in a south Indian population

Abstract: The authors find that APD assessed via the swinging flashlight test is a poor screening tool for glaucoma in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…A total of 31 articles from 30 studies met inclusion criteria (Fig 1). 4,15–44 Studies were conducted in more than 11 countries and published in different languages. We did not translate non-English articles, and 2 articles without an English abstract were excluded from this review.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 31 articles from 30 studies met inclusion criteria (Fig 1). 4,15–44 Studies were conducted in more than 11 countries and published in different languages. We did not translate non-English articles, and 2 articles without an English abstract were excluded from this review.…”
Section: Resultsmentioning
confidence: 99%
“…[5,26,27,29] Automated pupillometry records the precise amplitudes and latencies of pupil responses to stimulation using the same light intensity, analyzes these pupil responses, and converts the results of this analysis to RAPD scores without examiner bias. In this way, the technique offers more reliable assessment of RAPD.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies using pupillometric devices, Kalaboukhova et al 11 reported the presence of RAPD in 29% of glaucoma patients, Jonas et al 12 reported its presence in 41%, and Lankaranian et al 5 reported it in 56%. Using the swinging flash light test, Skorkovska et al 13 reported a rate of RAPD in glaucoma patients of 34%, Schiefer et al 2 a rate of 25%, Charalel et al 14 a rate of 66.7%, and Hennessy et al 15 a rate of 9.1%. The differences can be accounted for by the study methodologies, cut-off criteria, and subject populations.…”
Section: Discussionmentioning
confidence: 99%